PERTUMBUHAN TANAMAN KANTONG SEMAR (Nepenthes rafflesiana Jack.) DENGAN MODIFIKASI KONSENTRASI MEDIA DAN pH SECARA IN VITRO - Lea Yony Kunita; Susiyanti .; Sulastri Isminingsih; Yupi Isnaini (Jurnal Agroekoteknologi, 2011)
This research about growth of pichter plant Nepenthes rafflesiana Jack was aimed to determine the modification medium’s concentration and pH at in vitro . This research has been conducted in the laboratory of plant concervation center Bogor Botanical Garden. This research was doing from Juni to September 2010. research using randomized block design with 2 factor, the first factor is modification concentration medium MS, consisting of 5 level is 1 MS, 1/2 MS, 1/4 MS, 1/8 MS, dan 1/16 MS; and the second factor is the pH medium was consisted 3 level: pH 4,7, pH 5,7 dan pH 6,7 was repeated four times. The results showed that concentration medium 1/8 MS and all pH medium were significant the variable of number pichter, number rootlet, percentage of planlet life, percentage of planlet pichter, percentage of planlet rootlet.Key words: Nepenthes rafflesiana Jack, medium concentration, pH.